Towards post-war social science: contesting discourses and possible reconstruction for multicultural societies - Chandran, S. (University of Jaffna, 2012)
This paper tries to outline a framework for post-war social science amidst the contesting discourses. It also provides how the reorientation will assist in enhancing capacity and rebuild the society and polity in the multicultural context with particular reference to Sri Lanka. The ideological basis of social science is always traversed with multiple discourses and controversies when it emphasises self identity and self determination in plural set up. The theoretical framework has come right from classical foundations to post-modern manifestations. The inherent tension between value-free and value-laden approaches could not be transcended as both have their own strengths and weaknesses. Situating in the paradigm of developing society, Sri Lanka provides the scope for political integration rather social or cultural integration in the post-war rebuilding process. In this connection, the discipline of social science has its own moral responsibility in reorienting the multiple discourses. Taking history and political science as the case, five aspects can be discussed in the context of contesting discourses and possible reorientation and reconstruction. These include: history, self-identity, social conflict, political integration and development. These aspects can be in turn analysed in two broad paradigms as conflict model and consensus model. The moral foundations of social science seem to make dialogue between the wounded self and triumphant self. The whole challenge is related to construction of subjectivity in the light of ‘given rationality’ with future promises. At large, the social science must foster liberal democracy, federalism and multiculturalism. In other words, the beginning of capacity development is to foster these values in which the academicians have their say through social science disciplines.